The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1517/14728222.2015.1065818
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression in BRAF-mutated and wild-type metastatic melanoma and its correlation with response duration to BRAF inhibitors

Abstract: Objective: Currently, the treatment of BRAF V600-mutated metastatic melanoma with BRAF inhibitors gives a response rate of ~ 50% with a progression-free survival of ~ 6 -- 7 months. In order to identify predictive biomarkers capable of stratifying BRAF-mutated patients at high risk of shorter response duration to anti-BRAF therapy, the authors analyzed the expression of 15 microRNAs (miRNAs) targeting crucial genes involved in melanoma biology and drug response.Research design and methods: A total of 15 miRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…24 Through regulating gene expression, miRNAs can impact on different pathways associated with sensitivity or resistance to chemotherapeutic drugs in various tumors. [13][14][15][16][17] Several miRNAs, such as miR-106a, 25 miR-508-5p 26 and miRNA-19a/b 27 have been reported to play a role in the development of MDR in GC. However, miRNAs able to modulate the sensitivity to chemotherapy by regulating genes involved in the hypoxia signaling pathways have not yet been fully addressed in GC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Through regulating gene expression, miRNAs can impact on different pathways associated with sensitivity or resistance to chemotherapeutic drugs in various tumors. [13][14][15][16][17] Several miRNAs, such as miR-106a, 25 miR-508-5p 26 and miRNA-19a/b 27 have been reported to play a role in the development of MDR in GC. However, miRNAs able to modulate the sensitivity to chemotherapy by regulating genes involved in the hypoxia signaling pathways have not yet been fully addressed in GC.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Recently, microRNAs (miRNAs), small non coding RNAs that act as post-transcriptional repressors of gene expression, have been suggested to play essential roles in modulating chemotherapeutic tumor response. [13][14][15][16][17] We selected some miRNAs that recent literature and bioinformatics tools have highlighted to be involved in MDR1, HIF1A and HIPK2 gene modulation. Several studies have suggested the ability of miR-27a to modulate MDR1/P-gp expression [18][19][20] and the association of miR-181a deregulation with the modulation of HIPK2.…”
Section: Introductionmentioning
confidence: 99%
“…The tumors were most commonly epibulbar (27/37), and local invasion to eyelid skin occurred in four cases. The tumors were staged as T1 (27), T2 (6), and T3 (4). Median tumor thickness was 1.2 mm (range, 0.2-8.0 mm); the CM most commonly originated in a primary acquired melanosis with atypia (PAMĆ¾) (30/37), and a third of the CMs (12/37) were BRAF mutated (Table 1).…”
Section: Patient and Tumor Characteristicsmentioning
confidence: 99%
“…In BRAF-mutated patients treated with Vemurafenib, high expression of miR-192 and miR-193b* and low expression of miR-132 has been associated with short time to progression, indicating a poor prognosis [31].…”
Section: Mirnas Acting As Oncogenesmentioning
confidence: 99%